Solving international crime - Roden, Katie (Watts Books London, 1996)
International crime presents complex challenges due to its transnational nature, jurisdictional conflicts, and evolving criminal networks. In Solving International Crime, Roden explores the mechanisms by which law enforcement agencies, international organizations, and legal frameworks collaborate to combat crimes such as human trafficking, cybercrime, drug smuggling, and terrorism. The book examines the role of institutions like Interpol, Europol, and the United Nations, highlighting case studies that demonstrate successful cross-border investigations. Additionally, it discusses the impact of technology, intelligence sharing, and diplomatic cooperation in tracking and prosecuting international criminals. Roden argues that while significant progress has been made, continued innovation and policy reform are essential to addressing the growing sophistication of global crime.